The importance of vitamin D3 supplementation in orthopedics - literature review - Dominik Machaj; Katarzyna Cyboran; Alicja Płaczek; Marlena Baran; Michał Wojnowski (Kazimierz Wielki University, 2020)
Falls have been recognized by the WHO as one of the most significant problems in aging societies. In the elderly after 65 years of age, they cause 90% of the fractures of the proximal femoral bone (bkk) and 100% of the forearm fractures [5].They usually occur when walking (most often), getting up and sitting down. The consequences of falls, as well as themselves, can be prevented by supplementing vitamin D3 [6] [8] regulating the body's calcium-phosphate homeostasis. It improves neuromuscular function, including the mechanism reduces the frequency of falls. It also affects response time and balance. The concentration of vitamin D3 in the body is variable. Depends on endogenous biosynthesis and food supply. It also shows seasonal fluctuations. Its deficiencies lead to not only orthopedic and dental complications. It has been proven that there is a decreased level of 25 (OH) D3 in serum and such diseases as diabetes, hypertension, depression,neuro-degenerative diseases including Alzheimer's disease and increased likelihood of cancer, especially breast, prostate, and colon cancers [15].